Autonomous Learning for Proficiency Level İn Foreign Language Development of Graduate Students - Halil Küçükler (Indonesian Journal of EFL and Linguistics, 2016)
Also called student-centred learning, autonomous learning is a multifaceted and self-motivated study skill that relates to a change in focus in the learning environment from the teacher to the student or from teaching to learning (Taylor 2000, p. 107). Its impact on linguistic competence has been investigated over time and the two have been found to be correlated. This survey was conducted in Balıkesir University in academic years of 2014-2015. The survey analyses graduate (Master of Arts) students’ foreign language learning styles and strategies to find out to what extent they are autonomous. The aim of the study is to investigate the impacts of graduate students’ proficiency attitudes on autonomous learning in foreign language learning. Two kinds of questionnaires were administered: the first one was learner autonomy survey questionnaire developed by Zhang and Li (2004), which was administered to investigate how autonomous the participants were in learning English as a foreign language. The second one was the perceptual learning style preference questionnaire (PLSPQ), developed by Reid (1987). The two questionnaires were administered to 600 graduate students enrolled in the Institutions of Social Sciences and the Institution of Health at Balıkesir University in the academic years of 2014-2015. Only 504 graduate students responded. Then it was announced that there would be two types of English YDS preparation courses for the participants enrolled at Balıkesir University, Institute of M.A programs. 30 participants applied to join the courses. The participants are assigned to two groups, as instructed and non-instructed on voluntary bases. The study involved the YDS test that measured the performance of the control and experimental groups to find out the differences. The study involved 15 sample YDS tests that were administered after every two weeks of instructions. Before the training commenced, there were some preliminaries that were being applied to determine the advancement in the level of proficiency and the level of trainees.  The results indicate that the male graduate students from both groups performed better than the female learners. The results also reveal that the control group scored a mean of 38, 86 while the experimental group recorded 38, 06 in the first test. Throughout all tests, the experimental group only scores a few points less. The ultimate YDS (The formal Proficiency Exam) score was (control group= 48; experimental group =47), which is almost the same. There is no meaningful difference between the control and experimental group.